2020
DOI: 10.2147/idr.s226154
|View full text |Cite
|
Sign up to set email alerts
|

<p>Antifungal Activity of ZnO Nanoparticles and Nystatin and Downregulation of SAP1-3 Genes Expression in Fluconazole-Resistant <em>Candida albicans</em> Isolates from Vulvovaginal Candidiasis</p>

Abstract: Purpose: Antifungal resistance and virulence properties of Candida albicans (C. albicans) are growing health problems worldwide. The present study aims to investigate the effect of Zinc Oxide (ZnO) nanoparticles and Nystatin on SAP1-3 genes expression in C. albicans isolates of females with Vulvovaginal Candidiasis (VVC) isolated from Sayad Shirazi Obstetrics and Gynecology Hospital in Northeastern Iran during 2017-2018. Patients and Methods: In this descriptive-analytic study, vaginal samples were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 28 publications
(52 reference statements)
1
22
0
Order By: Relevance
“…In addition to efflux pumps, Candida species use other mechanisms for drug resistance. Overexpression of the ERG genes involved in the ergosterol biosynthesis and biofilm formation are two instances that result in drug resistance among Candida species 84,86–89 . Antifungal susceptibility testing prior to treatment could provide useful data for prescribing the proper antifungal drug, especially in confirmed cases of RVVC.…”
Section: Drug Resistance Among Candida Spp Causing Vvcmentioning
confidence: 99%
“…In addition to efflux pumps, Candida species use other mechanisms for drug resistance. Overexpression of the ERG genes involved in the ergosterol biosynthesis and biofilm formation are two instances that result in drug resistance among Candida species 84,86–89 . Antifungal susceptibility testing prior to treatment could provide useful data for prescribing the proper antifungal drug, especially in confirmed cases of RVVC.…”
Section: Drug Resistance Among Candida Spp Causing Vvcmentioning
confidence: 99%
“…As with silver nanoparticles, zinc nanoparticles show significant anti-candida effects both as a monotherapy [ 144 , 145 ] and in combination with antifungal drugs such as fluconazole [ 146 ]. Thus far, the in vitro antifungal activities of zinc nanoparticles have been evaluated with various strains of C. albicans, C. krusei, C. aprapsilosis, and C. tropicalis [ 116 , 144 , 147 ]. However, the in vivo studies remain unconvincing; as a result, zinc nanoparticles are currently not indicated for the treatment of a specific candidiasis.…”
Section: Metallic Nanoparticlesmentioning
confidence: 99%
“…ZnO INPs poses bactericidal activity against P. aeruginosa , E. coli , S. aureus , S. enterica , C. jejuni , and V. cholerae , antiviral activity against Herpes Simplex Virus Type 1 and hepatitis A virus, and antifungal activity against Botrytis cinerea , Penicillium expansum , Erythricium salmonicolor , and Candida albicans [ 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. ZnO nanoparticles in different ratios inhibited the growth of antibiotic-resistant Mycobacterium tuberculosis strains, but did not lead to bacterial death [ 98 ].…”
Section: Inps As Promising Antibacterial Agentsmentioning
confidence: 99%